On the way to restore Guatemala's degraded lands: Creating governance conditions. (December 2016) - Sales, Ebal; Rodas, Ogden; Valenzuela, Oscar; Hillbrand, Anique; Sabogal, César
Highlights: A multi-stakeholder roundtable is critical for inter-sectoral work. High-level political support is a key factor for the success of restoration in Guatemala. The PROBOSQUE Law provides a favourable legal framework and economic incentives for restoration at country level. Abstract: Guatemala is a megadiverse country but its ecosystems have been constantly threatened by stress factors. During the 1991–2001 period, the country experienced a forest loss of 93, 127 ha/year. This situation prompted the Government to set a target to restore 1.2 million ha of degraded land by 2045 and approved in 2015 a National Strategy for Forest Landscape Restoration. Findings show that the combination of a platform for dialogue and a legal framework (PROBOSQUE Law) to support restoration work on the ground has proved to be very important for the implementation of the National Strategy. Another key factor was the three-level approach that combined implementation activities at national, regional and local levels.